Did their Propertius walk that way? Ezra Pound's Homage to Sextus Propertius as a complaint against classical philology. (5th December 2018) - Dingee, William
Abstract: This article proposes to re-examine Ezra Pound's Homage to Sextus Propertius through the lens of Pound's response to classical philology in general and Latin textual criticism in particular. It begins by examining certain key details of Pound's education as an undergraduate and graduate student at the University of Pennsylvania and seeking to situate this background within the history of classical scholarship. It proceeds to examine aspects of Pound's aesthetic and political thinking as they relate to his opposition to philology and to his project in the Homage . In the main analytical section of the article, selected passages from the Homage are read as parodic appropriations of philological approaches to Latin texts, deployed in such a way as to forward a vision of Propertius very different from that predominant in the classical philology of Pound's student days. The conclusion of the article relates the Homage to Pound's broader project of creating a 'new method in scholarship' and considers the poem as an attempt to make a serious academic contribution to the study of Propertius.